Preparation method of nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst

By growing nickel-iron-based transition metal boride nanosheets on the quasi-two-dimensional black phosphorus surface, a nickel-iron-based transition metal boride/black phosphorus composite electrocatalyst was solved, and the problem of insufficient activity and stability of black phosphorus-based OER electrocatalysts was solved. Achieve efficient OER electrocatalytic performance.

CN119243237APending Publication Date: 2025-01-03CHINA JILIANG UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411367822.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The catalytic site activity of the quasi-two-dimensional black phosphorus-based OER electrocatalyst is not high and has poor stability in the O2 environment, and the Fe loss of nickel-iron-based catalyst is severe, affecting the electrochemical activity and stability.

Method used

Ethylene diamine-modified quasi-two-dimensional black phosphorus nanosheets were prepared by hydrothermal method, and nickel-iron-based transition metal boronide nanosheets were grown on their surface by chemical reduction method to construct nickel-iron-based transition metal boronide/black phosphorus composite analysis The electrocatalyst is used to improve the activity and stability of the catalyst.

Benefits of technology

The oxygen evolution reaction activity and stability of the electrocatalyst is significantly improved, the loss of Fe elements is inhibited, and the electrochemical activity and reaction kinetics are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243237A_ABST
    Figure CN119243237A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrocatalysis, and particularly relates to a preparation method of a nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst. The invention provides a preparation method of a ferronickel-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst, which is characterized by comprising the following steps: synthesizing a quasi-two-dimensional ethylenediamine modified black phosphorus nanosheet (eda-BP) by a hydrothermal method, and carrying out ultrasonic treatment on the surface of the obtained eda-BP to obtain the ferronickel-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst. The nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction (OER) electrocatalyst (Ni < x > FeyB / eda-BP) is prepared by loading nickel-iron-based transition metal boride (Ni < x > FeyB) through an in-situ chemical reduction method, so that modification of a two-dimensional black phosphorus electrocatalyst is realized; the problems of instability of a quasi-two-dimensional black phosphorus catalyst, serious Fe loss of a nickel-iron-based catalyst, poor reaction kinetics and the like are solved to a great extent, and under the synergistic effect of the two parts, the electro-catalytic oxygen evolution reaction activity and the electro-catalytic stability of the composite catalyst are remarkably improved. The preparation method of the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst provides a new thought and a new way for designing and developing a novel efficient and stable oxygen evolution reaction electrocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis, and specifically relates to a nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst and a preparation method thereof. Background Art

[0002] Hydrogen is a clean energy source that has attracted much attention. The use of electrocatalytic water splitting to produce hydrogen is a very effective means to solve the current global fossil energy shortage and environmental pollution problems. The water electrolysis process consists of two half reactions at the cathode and anode. The oxygen evolution reaction (OER) at the anode is the limiting factor in the water splitting hydrogen production process due to its slow kinetics. Therefore, it is very necessary to develop an efficient and stable OER electrocatalyst material.

[0003] Two-dimensional / quasi-two-dimensional materials have fully exposed active sites and are easy to coordinate with unsaturated metal sites, showing excellent performance in the field of catalysis. In recent years, the emerging non-metallic two-dimensional / quasi-two-dimensional material, black phosphorus (BP), has attracted much attention from the scientific research community. Phosphorus is one of the most abundant materials on Earth. Among the allotropes of phosphorus, layered BP materials are the most thermodynamically stable. Quasi-two-dimensional BP materials have a direct band gap that depends on the number of layers and an extremely high carrier mobility (usually greater than 200cm 2 V -1 s -1 ) and in-plane anisotropy are used in lithium-ion batteries, photovoltaic materials and photocatalysis. However, in the field of electrocatalysis, especially electrocatalytic OER, the research on quasi-two-dimensional BP-based materials is still in its initial stage compared with other two-dimensional / quasi-two-dimensional materials. Because quasi-two-dimensional BP has high carrier mobility, adjustable electronic structure and large specific surface area, it is a very promising OER electrocatalytic material, and its application in this area needs to be further developed.

[0004] However, the research on quasi-2D BP-based OER electrocatalysts still faces some challenges: (1) The activity of the quasi-2D BP catalytic sites is not high. Since the P element has a strong oxygen affinity, quasi-2D BP-based materials often face the problem of being resistant to OER oxygen-containing intermediates (such as * Oh, * OH, etc.) are too strongly adsorbed, while an ideal OER catalyst requires a moderate intermediate adsorption capacity; (2) Quasi-two-dimensional BP materials are not stable in an O2 environment. Studies have shown that O2 is the primary factor in the degradation of quasi-two-dimensional BP materials, while water has little effect on the degradation of quasi-two-dimensional BP materials. When quasi-two-dimensional BP reacts with O2, highly reactive superoxide ions (O2 - ); then O2 -It adsorbs to the surface phosphorus atoms to form PO bonds; finally, the PP bonds on the surface break and decompose. The oxidation process is accompanied by the degradation of the quasi-two-dimensional BP material and the decrease in conductivity, which leads to the instability of the electrochemical activity. Therefore, it is necessary to prepare BP-based composite materials to solve the above two key problems through the interaction between the two parts. In terms of the selection of composite materials, transition metal borides have competitive low OER overpotentials and are very promising OER catalyst materials. Among them, nickel-iron-based borides perform outstandingly, but due to the problem of Fe loss during the surface reconstruction of Fe-based catalysts, the interfacial reaction is affected, which limits the further improvement of the catalyst activity. Its composite with black phosphorus material is expected to inhibit the loss of Fe element and further improve the electrochemical activity.

[0005] The present invention proposes a method for improving the catalytic performance of quasi-two-dimensional BP materials. Firstly, a quasi-two-dimensional black phosphorus (eda-BP) nanosheet material modified with ethylenediamine is prepared by a hydrothermal method, and then a nickel-iron-based transition metal boride (Ni) is grown on its surface by a chemical reduction method. x Fe y B) Nanosheet materials, constructing transition metal boride / phosphorene (Ni) with 2D / 2D structure x Fe y B / eda-BP) composite oxygen evolution reaction electrocatalyst, the two parts play a synergistic role in greatly improving the activity and stability of the electrocatalyst. Summary of the invention

[0006] The present invention aims to obtain a nickel-iron-based transition metal boride (Ni x Fe y B) Composite of nanosheet material and quasi-two-dimensional black phosphorus (eda-BP) to achieve surface modification of eda-BP and prepare a high-performance nickel-iron-based transition metal boride / black phosphorus (Ni x Fe y The present invention firstly prepares ethylenediamine-modified quasi-two-dimensional eda-BP nanosheet material by a hydrothermal method using ethylenediamine as solvent, and then grows Ni on the surface of eda-BP by a chemical reduction method at room temperature. x Fe y B nanosheets, and the nickel-iron-based transition metal boride / black phosphorus (Ni x Fe y The composite oxygen evolution reaction electrocatalyst (B / eda-BP) has been developed. To a large extent, it solves the problems of poor oxygen evolution reaction activity and stability of quasi-two-dimensional BP materials, serious Fe loss and weak charge conduction ability of nickel-iron-based materials, and effectively improves the activity and stability of black phosphorus-based materials and nickel-iron-based materials in the oxygen evolution reaction process.

[0007] The present invention provides a nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst and a preparation method thereof, which is characterized by being achieved through the following technical solutions:

[0008] (1) First, ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) nanosheet powder was prepared by a solvothermal method. The specific process was as follows: 0.5 g of red phosphorus was fully ground in a mortar, then added to 75 mL of ethylenediamine and stirred vigorously for 30 minutes to form a uniform red phosphorus dispersion; the mixture was transferred to a 100 mL polytetrafluoroethylene liner and then placed in a stainless steel high-pressure reactor. After heating at 165°C for 24 hours, the reactor was placed in water and quickly cooled to room temperature; finally, the product was centrifuged and washed alternately with water and ethanol, and vacuum dried at 40°C for 6 hours to obtain black eda-BP powder.

[0009] (2) On the premise of obtaining the above-mentioned eda-BP powder, nickel-iron-based transition metal boride (Ni x Fe y B) loading, the specific operation process is as follows: under an ice water bath, a certain proportion and concentration of Ni(NO3)2·6H2O and FeSO4·7H2O (total concentration is 0.0025M) are dissolved in 20mL methanol to form a uniform solution; then a certain amount of eda-BP nanosheets (20mg-80mg) are added to the solution, and after ultrasonic dispersion for a period of time, a dispersion in which nickel ions and iron ions are fully adsorbed on the surface of eda-BP nanosheets is obtained; then, 5mL excess sodium borohydride (NaB H4) solution (0.015M) was slowly injected into the above dispersion under ice bath to obtain a nickel-iron-based transition metal boride / black phosphorus suspension with a Ni:Fe molar ratio of 1:3 to 3:1; finally, the precipitate was washed with deionized water to remove unreacted NaBH4; the suspension was centrifuged and vacuum dried at 40°C for 6h to obtain a black nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst; as a comparison, eda-BP powder was not added, and the other steps were the same as above to prepare a nickel-iron-based transition metal boride (Ni x Fe y B) Powder.

[0010] The advantages and positive effects of the present invention are:

[0011] The present invention modifies quasi-two-dimensional black phosphorus (eda-BP) electrocatalyst powder modified by ethylenediamine by combining with nickel-iron-based transition metal boride to prepare nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst, which has the advantages of obvious modification effect and low cost. Compared with other black phosphorus composite modification methods, the introduction of nickel-iron-based transition metal boride solves the problems of unstable electrochemical properties and low oxygen evolution reaction activity of quasi-two-dimensional black phosphorus catalyst to a large extent. At the same time, through the interaction between phosphorus and metal elements, the problems of serious Fe loss and poor reaction kinetics of nickel-iron-based catalyst are also solved. Under the synergistic effect of the two parts of the composite material, the electrocatalytic oxygen evolution reaction activity and electrocatalytic stability of the composite catalyst are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The transmission electron microscope (TEM) image of (a) ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) prepared in Example 1 and (b) TEM image of nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP);

[0013] Figure 2 It is the X-ray diffraction (XRD) pattern of the quasi-two-dimensional black phosphorus (eda-BP) modified by ethylenediamine, the nickel-iron-based transition metal boride (Ni3Fe1B) and the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1;

[0014] Figure 3 It is a Raman spectrum (Raman) of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP), nickel-iron-based transition metal boride (Ni3Fe1B) and nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1;

[0015] Figure 4 The (a) linear voltammetric sweep (LSV) curves, (b) electrochemical impedance spectroscopy (EIS) and (c) chronopotentiometry curves of the ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP), nickel-iron-based transition metal boride (Ni3Fe1B) and nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1;

[0016] Figure 5 is the Fe concentration in the electrolyte of the nickel-iron-based transition metal boride (Ni3Fe1B) and the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1 after electrochemical testing;

[0017] Figure 6 It is the change of phase angle of quasi-two-dimensional black phosphorus (eda-BP) modified by ethylenediamine, nickel-iron based transition metal boride (Ni3Fe1B) and nickel-iron based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1 at different potentials. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.

[0019] Embodiment 1:

[0020] (1) First, ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) nanosheet powder was prepared by a solvothermal method. The specific process was as follows: 0.5 g of red phosphorus was fully ground in a mortar, then added to 75 mL of ethylenediamine and stirred vigorously for 30 minutes to form a uniform red phosphorus dispersion; the mixture was transferred to a 100 mL polytetrafluoroethylene liner and then placed in a stainless steel high-pressure reactor. After heating at 165°C for 24 hours, the reactor was placed in water and quickly cooled to room temperature; finally, the product was centrifuged and washed alternately with water and ethanol, and vacuum dried at 40°C for 6 hours to obtain black eda-BP powder.

[0021] (2) On the premise of obtaining the above-mentioned eda-BP powder, nickel-iron-based transition metal boride (Ni3Fe1B) was loaded. The specific operation process was as follows: Ni(NO3)2·6H2O (0.00187M) and FeSO4·7H2O (0.00063M) were dissolved in 20mL of methanol in an ice-water bath to form a uniform solution; then a certain amount of eda-BP nanosheets (20mg) were added to the solution, and after ultrasonic dispersion for a period of time, a dispersion in which nickel ions and iron ions were fully adsorbed on the surface of eda-BP nanosheets was obtained; then, 5mL of excess sodium borohydride (NaBH4, 0.0015M) solution was slowly injected into the above dispersion under an ice bath to obtain a nickel-iron-based transition metal boride / black phosphorus suspension; finally, the precipitate was washed with deionized water to remove unreacted NaBH4; the suspension was centrifuged at 6000r / s and vacuum dried at 40°C for 6h to obtain a black nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst with a molar ratio of Ni and Fe of 3:1 and a mass ratio of Ni3Fe1B catalyst and eda-BP of 8:1; as a comparison, eda-BP powder was not added, and the other steps were the same as the above steps to prepare nickel-iron-based transition metal boride (Ni3Fe1B) powder.

[0022] Embodiment 2:

[0023] (1) The preparation process of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) powder is the same as that in Example 1.

[0024] (2) On the premise of obtaining the above-mentioned eda-BP powder, nickel-iron-based transition metal boride (Ni1Fe3B) was loaded. The specific operation process was as follows: Ni(NO3)2·6H2O (0.00063M) and FeSO4·7H2O (0.00187M) were dissolved in 20mL of methanol in an ice-water bath to form a uniform solution; then a certain amount of eda-BP nanosheets (20mg) were added to the solution, and after ultrasonic dispersion for a period of time, a dispersion in which nickel ions and iron ions were fully adsorbed on the surface of eda-BP nanosheets was obtained; then, 5mL of excess sodium borohydride (NaBH4, 0.0015M) solution was slowly injected into the above dispersion under an ice bath to obtain a nickel-iron-based transition metal boride / black phosphorus suspension; finally, the precipitate was washed with deionized water to remove unreacted NaBH4; the suspension was centrifuged at 6000r / s and vacuum dried at 40°C for 6h to obtain a black nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst with a molar ratio of Ni and Fe of 1:3 and a mass ratio of Ni1Fe3B catalyst and eda-BP of 8:1; as a comparison, eda-BP powder was not added, and the other steps were the same as the above steps to prepare nickel-iron-based transition metal boride (Ni1Fe3B) powder.

[0025] Embodiment 3:

[0026] (1) The preparation process of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) powder is the same as that in Example 1.

[0027] (2) On the premise of obtaining the above-mentioned eda-BP powder, nickel-iron-based transition metal boride (Ni1Fe1B) was loaded. The specific operation process was as follows: Ni(NO3)2·6H2O (0.00125M) and FeSO4·7H2O (0.00125M) were dissolved in 20mL of methanol in an ice-water bath to form a uniform solution; then a certain amount of eda-BP nanosheets (20mg) were added to the solution, and after ultrasonic dispersion for a period of time, a dispersion in which nickel ions and iron ions were fully adsorbed on the surface of eda-BP nanosheets was obtained; then, 5mL of excess sodium borohydride (NaBH4, 0.0015M) solution was slowly injected into the above dispersion under an ice bath to obtain a nickel-iron-based transition metal boride / black phosphorus suspension; finally, the precipitate was washed with deionized water to remove unreacted NaBH4; the suspension was centrifuged at 6000r / s and vacuum dried at 40°C for 6h to obtain a black nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst with a molar ratio of Ni and Fe of 1:1 and a mass ratio of Ni1Fe1B catalyst to eda-BP of 8:1; as a comparison, eda-BP powder was not added, and the other steps were the same as the above steps to prepare nickel-iron-based transition metal boride (Ni1Fe1B) powder.

[0028] Embodiment 4:

[0029] (1) The preparation process of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) powder is the same as that in Example 1.

[0030] (2) On the premise of obtaining the above-mentioned eda-BP powder, nickel-iron-based transition metal boride (Ni3Fe1B) was loaded. The specific operation process was as follows: Ni(NO3)2·6H2O (0.00187M) and FeSO4·7H2O (0.00063M) were dissolved in 20mL of methanol in an ice-water bath to form a uniform solution; then a certain amount of eda-BP nanosheets (40mg) were added to the solution, and after ultrasonic dispersion for a period of time, a dispersion in which nickel ions and iron ions were fully adsorbed on the surface of eda-BP nanosheets was obtained; then, 5mL of excess sodium borohydride (NaBH4, 0.0015M) solution was slowly injected into the above dispersion under an ice bath to obtain a nickel-iron-based transition metal boride / black phosphorus suspension; finally, the precipitate was washed with deionized water to remove unreacted NaBH4; the suspension was centrifuged at 6000r / s and vacuum dried at 40°C for 6h to obtain a black nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst with a molar ratio of Ni and Fe of 3:1 and a mass ratio of Ni3Fe1B catalyst and eda-BP of 4:1; as a comparison, eda-BP powder was not added, and the other steps were the same as the above steps to prepare nickel-iron-based transition metal boride (Ni3Fe1B) powder.

[0031] Embodiment 5:

[0032] (1) The preparation process of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) powder is the same as that in Example 1.

[0033] (2) On the premise of obtaining the above-mentioned eda-BP powder, nickel-iron-based transition metal boride (Ni3Fe1B) was loaded. The specific operation process was as follows: Ni(NO3)2·6H2O (0.00187M) and FeSO4·7H2O (0.00063M) were dissolved in 20mL of methanol in an ice-water bath to form a uniform solution; then a certain amount of eda-BP nanosheets (80mg) were added to the solution, and after ultrasonic dispersion for a period of time, a dispersion in which nickel ions and iron ions were fully adsorbed on the surface of eda-BP nanosheets was obtained; then, 5mL of excess sodium borohydride (NaBH4, 0.0015M) solution was slowly injected into the above dispersion under an ice bath to obtain a nickel-iron-based transition metal boride / black phosphorus suspension; finally, the precipitate was washed with deionized water to remove unreacted NaBH4; the suspension was centrifuged at 6000r / s and vacuum dried at 40°C for 6h to obtain a black nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst with a molar ratio of Ni and Fe of 3:1 and a mass ratio of Ni3Fe1B catalyst and eda-BP of 2:1; as a comparison, eda-BP powder was not added, and the other steps were the same as the above steps to prepare a nickel-iron-based transition metal boride (Ni3Fe1B) powder.

[0034] The electrocatalytic oxygen evolution reaction performance of the ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP), nickel-iron-based transition metal boride (NixFeyB) and nickel-iron-based transition metal boride / black phosphorus composite electrocatalyst (NixFeyB / eda-BP) prepared by the present invention is tested by using an electrochemical workstation and a three-electrode test system. The specific process and steps are as follows: first, the electrode material is prepared, 5 mg of catalyst powder is dispersed in ethanol (600 μL), and ultrasonic dispersion is performed for 5 minutes to form a uniform catalyst ink, and then 30 μL of the catalyst ink is coated on a 1×1 cm 2 On nickel foam substrate (catalyst loading 1.0 mg cm -2 ), and drying to obtain the electrode material; in the electrochemical test, 1M KOH was used as the electrolyte, the Ag / AgCl electrode was used as the reference electrode, and the graphite rod was used as the counter electrode to form a three-electrode test system, which was connected to an electrochemical workstation for electrocatalytic performance test and evaluation.

[0035] Figure 1The transmission electron microscope (TEM) images of (a) ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) prepared in Example 1 and (b) nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) are shown in FIG. As can be seen from the figure, the quasi-two-dimensional black phosphorus (eda-BP) sample modified by ethylenediamine is in the form of a thin sheet with a size between 100 and 200 nm, while in the transmission electron microscope of the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP), it can be clearly observed that the thin nickel-iron-based transition metal boride (Ni3Fe1B) with wrinkles is evenly covered on the surface of black phosphorus, forming a good heterogeneous contact, which is conducive to the rapid conduction of charge from the quasi-two-dimensional black phosphorus (eda-BP) modified by ethylenediamine to the nickel-iron-based transition metal boride (Ni3Fe1B).

[0036] Figure 2 X-ray diffraction (XRD) patterns of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP), nickel-iron-based transition metal boride (Ni3Fe1B), and nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1. It can be seen from the figure that each diffraction peak of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) corresponds to orthorhombic black phosphorus (JCPDS No.76-196332), and the peak at a small diffraction angle of 2θ=10.1° indicates an intercalation modified by ethylenediamine. It can be seen from the figure that nickel-iron-based transition metal boride (Ni3Fe1B) has no obvious diffraction peak, which is consistent with its amorphous characteristics, while the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) has the diffraction characteristic peak of quasi-two-dimensional black phosphorus modified with ethylenediamine, and its peak intensity is weakened. This is mainly due to the coverage of nickel-iron-based transition metal boride on quasi-two-dimensional black phosphorus (eda-BP) modified with ethylenediamine.

[0037] Figure 3 The Raman spectra of the quasi-two-dimensional black phosphorus (eda-BP) modified with ethylenediamine, the nickel-iron transition metal boride (Ni3Fe1B), and the nickel-iron transition metal boride / black phosphorus composite electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1 are shown in Figure 1. It can be seen from the figure that the sample nickel-iron transition metal boride / black phosphorus composite electrocatalyst (Ni3Fe1B / eda-BP) has a Raman spectrum of 362, 440, 466 cm -1The Raman characteristic peaks belonging to ethylenediamine-modified black phosphorus (eda-BP) appeared at the peak positions, confirming that the orthorhombic phase structure of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) was still retained in the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP), which was consistent with the XRD results. -1 The peak at is due to the formation of PO bonds during the inevitable oxidation process.

[0038] Figure 4 The (a) linear voltammetric sweep (LSV) curves, (b) electrochemical impedance spectroscopy (EIS) and (c) chronopotentiometry curves of the ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP), nickel-iron-based transition metal boride (Ni3Fe1B) and nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1. Figure 4 (a) It can be seen that the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) has a larger current density at a smaller voltage and exhibits the best electrocatalytic activity. Its performance is better than that of the single nickel-iron-based transition metal boride (Ni3Fe1B) and far exceeds the performance of quasi-two-dimensional black phosphorus (eda-BP) modified with ethylenediamine. Figure 4 Based on the electrochemical impedance spectroscopy in (b), it is clearly shown that the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) has the smallest impedance arc semicircle radius, indicating that the introduction of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) significantly accelerates the charge transfer kinetics between the electrode surface and the electrolyte during the electrocatalytic process. This explains Figure 4 (a) The reasons for the excellent catalytic performance of nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP). Figure 4 (c) It can be seen that at 10mAcm -2 The stability of three samples, ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP), nickel-iron-based transition metal boride (Ni3Fe1B), and nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP), were tested by chronopotentiometry at a constant current density of . Among them, the stability of nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) is much better than that of other samples, and there is no significant change in potential during the 60-hour operation, which is attributed to the surface coating of nickel-iron-based transition metal boride (Ni3Fe1B) preventing the degradation of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP).

[0039] Figure 5The Fe concentration in the electrolyte of the nickel-iron-based transition metal boride (Ni3Fe1B) and the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) prepared in Example 1 after electrochemical testing. It can be seen from the figure that the Fe concentration dissolved in the nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) electrode after two hours of polarization under constant current conditions is 93.55 mg L -1 The dissolved Fe concentration of the nickel-iron transition metal boride (Ni3Fe1B) electrode is 273.28 mg L -1 , indicating that the interface engineering of ethylenediamine-modified quasi-two-dimensional black phosphorus (eda-BP) effectively suppressed the Fe loss of nickel-iron-based transition metal boride (Ni3Fe1B), resulting in more stable reaction interface kinetics, explaining Figure 4 (c) Causes of stability.

[0040] Figure 6 It is the change of phase angle of quasi-two-dimensional black phosphorus (eda-BP) modified by ethylenediamine, nickel-iron transition metal boride (Ni3Fe1B) and nickel-iron transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) at different potentials prepared in Example 1. As can be seen from the figure, with the increase of the electrode applied voltage, the phase angle of the three samples gradually decreases, indicating that the reaction kinetics increases with the increase of voltage. Compared with the nickel-iron transition metal boride (Ni3Fe1B) sample, the phase angle of the nickel-iron transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) decreases faster with the increase of voltage, while the rate of change of the quasi-two-dimensional black phosphorus (eda-BP) sample modified by ethylenediamine is the lowest. The reaction kinetic results illustrate that the water decomposition reaction kinetics of the nickel-iron transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni3Fe1B / eda-BP) is the strongest.

Claims

1. A method for preparing a nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst, characterized in that The method is achieved by the following technical scheme: (1) 0.5 g of red phosphorus solid powder is placed in a mortar and ground into a relatively fine powder, then transferred to ethylenediamine, and after vigorous stirring for 30 min, the mixture is transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene and heated at 165°C for 24 h; after the reaction is completed, the autoclave is quickly cooled to room temperature, then washed by alternating centrifugation with water and ethanol, and finally dried in vacuum at 40°C for 6 h; (2) dispersing the ethylenediamine-modified quasi-two-dimensional black phosphorus nanosheet (eda-BP) powder prepared in the above step (1) in a methanol solution containing Ni(NO3)2·6H2O and FeSO4·7H2O to form a uniform dispersion, and then subjecting the dispersion to ultrasonic treatment to allow nickel ions and iron ions to be fully adsorbed on the surface of the eda-BP nanosheet; subsequently placing the dispersion in an ice water bath, and slowly injecting a stoichiometric excess of NaBH4 (0.015M, 5mL) solution into the dispersion with a syringe to obtain a black precipitate; washing the precipitate with deionized water by centrifugation to remove unreacted NaBH4, and finally drying under vacuum at 40°C for 6h to prepare a nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst (Ni x Fe y B / eda-BP).

2. A nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst prepared according to claim 1, characterized in that: The transition metal boride / phosphorene composite oxygen evolution reaction electrocatalyst is composed of a two-dimensional transition metal boride sheet material coated on a quasi-two-dimensional black phosphorus nanosheet.

3. The method for preparing a nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst according to claim 1, characterized in that: The rapid cooling described in step (1) is carried out by placing the reaction kettle in ice water at 0°C.

4. The method for preparing a nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst according to claim 1, characterized in that: In the methanol solution containing Ni(NO3)2·6H2O and FeSO4·7H2O described in step (2), the molar concentration ratio of Ni(NO3)2·6H2O to FeSO4·7H2O is 1:3, 1:1 and 3:

1.

5. The method for preparing a nickel-iron-based transition metal boride / black phosphorus composite oxygen evolution reaction electrocatalyst according to claim 1, characterized in that: The mass ratio of the NixFeyB catalyst to eda-BP in step (2) is 2:1, 4:1 and 8:1.

Citation Information

Cited By

  • Preparation method and application of CoO / black phosphorus catalyst

    CN120054551A

  • Preparation method and application of CoO / black phosphorus catalyst

    CN120054551B

  • Electrocatalytic water decomposition device with nickel hydroxide / amorphous black phosphorus electrode

    CN121362998A